The Intersection of Dayak Tarangk Customary Divorce Practices and Canon Law - Dandi, Yohanes; Dendri, Dendri; Endi, Yohanes (Jurnal Hukum Magnum Opus, 2025)
This research is motivated by the phenomenon of divorce which often occurs to overcome problems in family life. This study was conducted to analyze Tarangk Customary Law regarding divorce and elaborated from the perspective of Catholic Church teachings. The existence of laws regarding divorce in Tarangk Customary Law becomes a problem when compared with Church Law. The aim of this research is to find out the pastoral steps taken by the Catholic Church in dealing with problems that occur, especially regarding domestic problems that lead to divorce. The author uses a qualitative descriptive research method to describe the Tarangk Customary Law regarding divorce and the Church's teachings regarding marriage as well as finding a solution. The main source used in this study is the Book of Canon Law, while supporting sources are several relevant scientific articles and books. The author found that the Catholic Church took pastoral steps by 1) holding Marriage Preparation Courses (MPC), 2) providing catechesis on Catholic marriage, 3) providing sexuality education, 4) involving community leaders and catechists to proclaim the Church's teachings on marriage, 5) renewing marriage vows, 6) and making an agreement to give equal respect to Church law and customary law. These pastoral steps, especially in addressing the Tarangk Customary Law regarding divorce, can be used by Churches that have such pastoral challenges.